Pengaruh Penambahan Madu Dalam Pakan Induk Jantan Lobster Air Tawar Red Claw (Cherax quadricarinatus) Terhadap Rasio Jenis Kelamin Larva [The Effect Of Suplementation Of Honey In Feed Of Male Mains Fresh Water Cray Fish Red Claw (Cherax quadricarinatus) To Larva Sex Ratio ] - A.Taufiq Mukti; A.Shofy Mubarak; Adde Ermawan (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract The aim of this research was to know the effect of honey supplementation in feed of male main freshwater cray fish red claw to larva sex ratio and the level of survival of freshwater cray fish and to get the best doses of honey to give highest male sex ratio. This research was done at Laboratory of Fishery Education, Fishery and Marines Faculty, Airlangga University in October 2007 until March 2008. Methods of this research was experimental and used completely randomized designed with 7 treatments. Giving of honey with differences doses were A ( 0 ml/kg) control, B ( 50 ml /kg), C ( 100 ml /kg), D ( 150 ml /kg), E ( 200 ml /kg), F ( 250 ml/kg) and G ( 300 ml/kg) which each treatment got three times replicated. Data processed by Analysis of Variance (ANOVA). The result of this research showed that supplementation of honey in feed male main freshwater cray fish red claw not significantly different to larva sex ratio and survival rate of freshwater cray fish. Otherwise, result of the supplementation of honey in feed of male main freshwater cray fish showed the increasingly male sex ratio of freshwater cray fish red claw larvae.